ANALISIS PRINSIP DESAIN VISUAL PADA INSTAGRAM @KOMINFOBOGOR UNTUK MENYAMPAIKAN INFORMASI KEPADA PUBLIK - Bainuri, Zaidan Halifz; Bachtiar, Willy (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2025)
The development of social media has encouraged the Bogor City Communication and Information Office to utilize Instagram as a means to convey information through visual content. This study aims to describe how visual design principles such as unity, balance, rhythm, and emphasis are applied in the content of @kominfobogor uploads. This study uses a qualitative approach with content analysis techniques and purposive sampling of uploads from January to April 2025. The results of the analysis show that uploads on the @kominfobogor account have optimally applied visual design principles, such as the feed designs